2018
DOI: 10.5217/ir.2018.16.1.99
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of dietary fiber and fecal fiber components including pH in rural Africans with colorectal cancer

Abstract: Background/AimsColorectal cancer (CRC) is now a major public health problem with heavy morbidity and mortality in rural Africans despite the lingering dietary fiber-rich foodstuffs consumption. Studies have shown that increased intake of dietary fiber which contribute to low fecal pH and also influences the activity of intestinal microbiota, is associated with a lowered risk for CRC. However, whether or not the apparent high dietary fiber consumption by Africans do not longer protects against CRC risk is unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Fecal pH was lowest ( P < 0.05) for cats consuming the 10C treatment. This result was interesting as differences were expected for the 15C treatment rather than the 10C treatment as previous studies reported increased fiber intake associated with lower fecal pH ( Faruk et al, 2018).…”
Section: Resultsmentioning
confidence: 54%
“…Fecal pH was lowest ( P < 0.05) for cats consuming the 10C treatment. This result was interesting as differences were expected for the 15C treatment rather than the 10C treatment as previous studies reported increased fiber intake associated with lower fecal pH ( Faruk et al, 2018).…”
Section: Resultsmentioning
confidence: 54%
“…Often, low transit rate and low BSS accompany with high abundance of Akkermansia [ 17 , 45 ]. Furthermore, constipation and high faecal pH may be related to colorectal cancer (Tabel 1) [ 3 , 40 ]. In accordance with this, enhanced growth of Akkermansia at high pH and slow dilution rates was demonstrated in in vitro cultivation experiments with faecal cultures [ 15 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the previously described poor healing of fistulae resulting from CD, the use of FMT in these patients may be a breakthrough in its treatment. Moreover, it seems important to use FMT to reduce diarrhea, and to implement fiber supplementation, which will increase stool volume, thus preventing feces from entering the fistula and the overgrowth of bacterial species [65,84]. Probiotics, in turn, due to their ability to lower glycaemia and cholesterol [55,56], seem to be helpful in patients with RVF and concomitant diabetes or hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fiber actually has an effect on stool volume due to the reduction in the concentration of substances such as bile acid. The stool of patients taking dietary fiber is harder than that of patients not taking it [84]. Moreover, increased fiber intake leads to a decrease in fecal pH [85].…”
Section: Stoma and Stool Featuresmentioning
confidence: 99%